2017
DOI: 10.1016/j.ejmech.2016.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and SAR evaluation of novel thioridazine derivatives active against drug-resistant tuberculosis

Abstract: The neuroleptic drug thioridazine has been recently repositioned as possible anti-tubercular drug. Thioridazine showed anti-tubercular activity against drug resistant mycobacteria but it is endowed with adverse side effects. A small library of thioridazine derivatives has been designed through the replacement of the piperidine and phenothiazine moieties, with the aim to improve the anti-tubercular activity and to reduce the cytotoxic effects. Among the resulting compounds, the indole derivative 12e showed an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…In recent years a wide range of factors has led to the resurgence of TB. The causative pathogen Mtb afflicts more frequently patients with weakened immune system and thus, TB is significantly hazardous to those who suffer from the human immune deficiency virus (HIV) [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years a wide range of factors has led to the resurgence of TB. The causative pathogen Mtb afflicts more frequently patients with weakened immune system and thus, TB is significantly hazardous to those who suffer from the human immune deficiency virus (HIV) [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the high cost of conventional therapy constitutes a serious problem. Hence, it is obvious that there is an imperative need to design new agents with antitubercular activity in order not only to tackle the resistant strains of Mtb, but also to reduce the therapy period [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of a study to identify novel antibacterial agents designed to overcome antimicrobial resistance, a small library of diverse bioactive compounds had previously been synthesised within our team. Using the Resazurin Microtiter Assay (REMA) [14,15,16], these compounds were screened for antibacterial activity at a fixed concentration (128 μg/mL) against a range of drug-susceptible bacteria including Gram-positive, Gram-negative and mycolata bacteria (Supporting Information, Table S1) which revealed that many possessed little utility, even at these high concentrations. However, benzo-[2,1,3]-diazole architectures 1 – 12 were shown to possess antibacterial activity, including activity against mycolata bacteria and Mtb (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…However, thioridazine and other phenothiazines inhibit Ca 2ϩ ion channels and are used as antipsychotic drugs (24); hence, they have side effects and are cytotoxic at low concentrations. For example, the 50% inhibitory concentration (IC 50 ) of thioridazine for human macrophages is 5 to 8 g/ml (24,78,81). An additional cytotoxic mechanism of many drug efflux pump inhibitors is that they impair host transporter proteins (82).…”
Section: Discussionmentioning
confidence: 99%